Tantangan Teknologi Dalam Pelaksanaan Manajemen Arsip Berbasis Elektronik/Digital - Baidawi, Ahmad Hafi; Anastasya, Aldita (CV. Dalle’ Deceng Abeeayla, 2025)
This study sought to identify the digital issues associated with establishing digital archive data management. This study employs library research, which involves gathering data information using documentation procedures, specifically searching for data on important topics in a large number of journals or scientific papers. According to the preceding findings and studies, electronic archive management in Indonesia is divided into four stages: production and preservation, dissemination and utilization, maintenance, and disposition. The implementation of digital-based archives has not been carried out optimally due to obstacles such as a lack of understanding of digital archives, limited human resource capabilities in managing digital-based archives, and a lack of adequate facilities and infrastructure to support digital-based archive management.